Identification lncRNA LOC102551149/miR‐23a‐5p pathway in hepatic fibrosis. (15th May 2020) - Dong, Zhiheng; Li, Sha; Si, Lengge; Ma, Ruilian; Bao, Lidao; Bo, Agula
Abstract: Background: Hepatic fibrosis is a worldwide incurable disease; due to the complex and unclear mechanism, there lack the effective therapeutic targets. However, the mechanism of miR‐23a‐5p underling this pathological process is largely not clear. The purpose of this study was to investigate the role of miR‐23a‐5p in hepatic fibrosis and HSC activation. Methods: The content of miR‐23a‐5p in hepatic fibrosis induced by N‐nitrosodimethylamine (NDMA) and HSC activation induced by platelet‐derived growth factor (PDGF) was detected by qRT‐PCR. H&E staining, Masson staining and Shear wave electrography (SWE) were used to detect the degree of hepatic fibrosis. Immunohistochemistry staining, qRT‐PCR and Western blot detect the related markers of liver fibrosis or HSC activation, as well as the related pathway genes and proteins. Dual‐luciferase reporter system verifies the interaction between miR‐23a‐5p with PTEN or miR‐23a‐5p with lncRNA LOC102551149 in HSC‐T6. siRNA and miRNA mimic transfer to HSC‐T6 to detect the function of lncRNA LOC102551149 and miR‐23a‐5p on HSC activation. Results: After hepatic fibrosis and HSC activation happened, the expression of miR‐23a‐5p was up‐regulated, whereas anti‐miR‐23a‐5p can alleviate hepatic fibrosis and HSC activation. Further research shows miR‐23a‐5p can target PTEN and degrade it, causing activation of PI3K/Akt/mTOR/Snail pathway. lncRNA LOC102551149 can be used as a competition endogenous RNA (ceRNA) targeting miR‐23a‐5p through base pairing, and siRNA LOC102551149 or exogenous miR‐23a‐5p can induce HSC activation through PI3K/Akt/mTOR/Snail pathway. Conclusion: We demonstrate mechanism pathway of miR‐23a‐5p on hepatic fibrosis and HSC activation, which may develop a therapeutic target for hepatic fibrosis.